Effect of aluminium oxide and silicon carbide abrasive type on mild steel surface temperature - Mohd Hizam, Mohd Noor (2010)
Surface grinding is a finishing process used to improve surface finish, abrade hard materials, and tighten the tolerance on flat surfaces by removing a small amount of material. The phenomena of removing process actually will lead to the thermal damage to work piece and wheel grinder. As a result, this study tends to investigate the optimum parameter on mild steel grinding process by using conventional grinding machine through understanding the thermal effect and temperature distribution in the process and to investigate the thermal process of the mild steel grinding process for different parameter by using aluminum oxide and silicon carbide as a wheel grinder by running the experiment in dry grinding. A method of capturing the increasing temperature value is by using infrared thermometer. Depth of cut and table speed are the variables parameter used in this experiment and spindle speed and mode of dressing are the parameter that constant along the experiment are running. Furthermore, by using Taguchi approached, design of experiment (DOE) will be attained and Minitab software is used to design the DOE. Two way ANOVA methods then used to make an analysis of the data attained. The temperature value are analyzed to make the conformation that table speed and silicon carbide wheel grinder will give high impact to temperature rising. This research proved that by using silicon carbide as a grinding wheel, it will give higher thermal effect to the workpiece instead using aluminium oxide grinding wheel. Silicon carbide wheel grinder, that have rough grain will produce high friction force during grinding process occur. This friction force then will produce heat and will produce higher value of temperature instead using aluminium oxide. Aluminium oxide that have smaller grain, will also produce heat but the value of the temperature are smaller than using silicon carbide. After that, table speed is most significant factor that effect thermal on mild steel grinding process with silicon carbide as wheel grinder but for aluminium oxide wheel grinder, thermal effect are very low when using variablesparameter.